Metamaterial properties of Babinet complementary complex structures - Tóth Emese; Bánhelyi Balázs; Fekete Olivér; Czirjákné Csete Mária (2023)
Single and multiple layers of sub-wavelength periodic Babinet complementary patterns composed of rounded nano-object miniarrays were investigated. In case of illumination with linearly and circularly polarized light the azimuthal orientation and handedness (in)dependence of (cross-polarized) copolarized transmitted signal components was proven for all types of patterns. Considerable (weak) asymmetric transmission was demonstrated in extended bands exclusively for both types of copolarized (cross-polarized) signals transmitted through single layer of convex miniarrays. Three-dimensional structures constructed with convex–concave–convex complex pattern-layers resulted in a negative index at the visible region boundary both for linearly and circularly polarized light illuminations. This is because dipolar modes on the convex nano-objects are synchronized with co-existent reversal dipoles on the concave nano-objects via interlayer coupling. Although during linearly polarized light illumination, the interlayer interaction decouples the localized and propagating modes excitable on the concave pattern in the 90° azimuthal orientation, the synchronization via tilted-rotating nanoring dipoles is almost perfect in the 0° azimuthal orientation. For circularly polarized light illumination, both the dispersion maps and the negative index phenomena synthesize the characteristics of the two orthogonal linearly polarized light illuminations. Important aspect is the appearance of a small/intermediate (large) time-averaged amplitude magnetic dipole due to the tilted (twisted) electric dipole on the concave nanoring, which less/more quickly turns (continuously rotates) with large/intermediate (small) out-of-plane tilting, when illumination is realized with linearly polarized light in the 90°/0° azimuthal orientation (with circularly polarized light). The location of the negative index can be predicted based on the copolarized transmittance signals computed for circularly polarized light illumination by using the linear base representation of Jones transmission matrix elements.
Keywords: Fizikai tudományok